The Routledge handbook of economic expectations in historical perspective - Lenel, Laetitia; Nützenadel, Alexander; Streb, Jochen; Köhler, Ingo (Routledge, Taylor & Francis Group, 2026)
"The Routledge Handbook of Economic Expectations in Historical Perspective offers a one-stop reference that distills and summarizes the recent scholarship on economic expectations. Investigating the dynamics, effects, and determinants of economic expectations from a global perspective since the seventeenth century, the book enhances the understanding of expectation formation across time and space. Expectations drive economic decision-making-and thus offer a fundamental key to understanding economic behavior. Given the centrality of economics to society, the historical study of economic expectations is a highly relevant endeavor, for which this volume provides an accessible starting point. Featuring 33 chapters written by leading scholars from fields ranging from anthropology to political science, this handbook provides a uniquely interdisciplinary perspective. Together, the collection of essays argues that the development of economic theory and empirical research on expectation formation has not taken place in a vacuum. Rather, it must be understood as one strand in a complex entanglement of knowledge production, experiences, and economic and political decision-making, which interacted with, challenged, and transformed each other. With its broad scope, this handbook will be of interest to students and scholars across multiple disciplines including economic history, economics, sociology, anthropology, psychology, and political science"--